Zambia : Public Expenditure Management and Financial Accountability Review - World Bank (Washington, DC, 2013)
The challenges faced by Zambia in public expenditure management (PEM) have been longstanding, and will require targeted efforts, as well as a strong degree of political will to address. The recently launched constitutional review, which includes issues of public finance, the anti-corruption campaign of the new Government, and the renewed interest by Parliament in governance issues, and accountability have all been encouraging steps. Nevertheless, for Zambia to assure that public accountability is enduring, and not dependent upon the Government of the day, it must take steps to strengthen institutions of the State that can provide public oversight, and that promote basic checks and balances. This report provides a very detailed analysis of the country's PEM, and accountability processes. Yet, many of the recommendations are not new, but have been cited in previous reports of the Bank, and/or other donors. Effective implementation of public sector reforms will likely remain a challenge in Zambia. The limited capacity of Government suggests the need to target a few major aspects of public finance, and to address them persistently: improving compliance with existing regulations; strengthening the oversight institutions of the State; promoting public access to information; and, rebuilding information management, and reporting systems. The report also deals with the second objective of the Poverty Reduction Strategy Paper (PRSP), i.e., with ways and methods by which the Government can ensure efficient, equitable, and transparent management of public resources. It also focuses on the dimension of governance, i.e., the effectiveness of government to be able to provide public services. The specific objectives of the report are to: (a) provide a comprehensive and integrated assessment of Zambia's overall fiduciary risk, i.e., budget management, financial systems and auditing, and public procurement; (b) document PEM reforms progress to-date, and challenges facing Zambia; and, (c) develop a realistic action plan, outlining short and medium term remedial measures, which the Government should implement with donor support.